SURXONDARYO VOHASI YERYONG‘OQ O‘SIMLIGIDA UCHROVCHI NEMATODA TURLARINING BARQARORLIK CHASTOTASI VA DOMINANTLIK DARAJASI BO‘YICHA TAHLILI - Xurramov Alisher Shukurovich , Xurramov Alisher Shukurovich; Choriyev Siroj Hamzayevich , Choriyev Siroj Hamzayevich (Actual problems and prospects of the study of the fauna, 2024)
In the article, 136 species of nematodes were registered in the root and rhizosphere of peanut plants in the Surkhandarya region. Identified nematode species were analyzed according to persistence frequency (Tichler scale) and dominance level (Kasprzak and Niedbala scale).